2003
DOI: 10.1172/jci15211
|View full text |Cite
|
Sign up to set email alerts
|

The role of endothelial insulin signaling in the regulation of vascular tone and insulin resistance

Abstract: Conflict of interest:The authors have declared that no conflict of interest exists. Nonstandard abbreviations used: insulin receptor (IR); endothelin-1 (ET-1); vascular endothelial cell insulin receptor knockout (VENIRKO); glucose-tolerance test (GTT); insulintolerance tests (ITT); systolic blood pressure (SBP); mean blood pressure (MBP); diastolic blood pressure (DBP); heart rate (HR); glucose infusion rate (GIR); lipoprotein lipase (LPL). these animals and explore the role of the insulin receptor in retinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
166
0
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 305 publications
(184 citation statements)
references
References 51 publications
13
166
0
5
Order By: Relevance
“…such as the liver (44). The current study also demonstrated that selective insulin resistance appears to increase serine phosphorylation of IRS1/2.…”
Section: Discussionsupporting
confidence: 76%
“…such as the liver (44). The current study also demonstrated that selective insulin resistance appears to increase serine phosphorylation of IRS1/2.…”
Section: Discussionsupporting
confidence: 76%
“…Ocular circulation is largely controlled by autoregulative mechanisms, which maintain a stable retinal and to a large extent choroidal and optic nerve blood supply [19]. In the case of carotid atherosclerosis and OCAD, chronic cerebral hypotension can induce a down- ward shift of the cerebral and ocular vascular autoregulation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, IRS-1 knockout mice that have an expected metabolic phenotype of insulin resistance [42] are also hypertensive with impaired endothelium-dependent vasodilation [43]. Finally, transgenic mice with endothelial specific ablation of the insulin receptor have a metabolic phenotype of insulin resistance on either a low-salt or high-salt diet, suggesting that insulin signaling in vascular endothelium contributes to insulin-mediated glucose disposal in certain contexts [44].…”
Section: Signaling Pathwaysmentioning
confidence: 99%